Curriculum and production of a qualitative research habitus amongst Sociology graduate students - Meo, Analía Inés; Dabenigno, Valeria (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2015)
This article analyses the outline of an undergraduate qualitative research module, reflecting on how it could contribute to shaping a "qualitative research habitus" amongst students by assuming the role of researchers. Firstly, it unpacks the ways in which the research-teaching nexus has been approached in other national contexts. Secondly, it examines the assumptions, objectives, and delivery of the course outline. In so doing, it focuses on the nature, scope and expected learning outcomes of a wide variety of individual and collective research exercises structuring the module. It is argued that this course outline is an example of a "research-based teaching" that could contribute to the development of a dialogic, reflexive and situated approach to social research by undergraduate sociology students from Buenos Aires University